Manual and semi-automated approaches to MIBG myocardial scintigraphy in patients with Parkinson’s disease - Boccalini, Cecilia; Carli, Giulia; Vanoli, Emilia Giovanna; Cocco, Antoniangela; Albanese, Alberto; Garibotto, Valentina; Perani, Daniela (Frontiers in Medicine, 2022)
Objective: This study investigates the effects of manual and semiautomatic methods for assessing MIBG semi-quantitative indices in a clinical setting. Materials and Methods: We included MIBG scans obtained in 35 patients with idiopathic Parkinson’s Disease. Early and late heart-to-mediastinum (H/M) ratios were calculated from MIBG images using regions of interest (ROIs) placed over the heart and the mediastinum. The ROIs were derived using two approaches: (i) manually drawn and (ii) semiautomatic fixed-size ROIs using anatomical landmarks. Expert, moderate-expert, and not expert raters applied the ROIs procedures and interpreted the MIBG images. We evaluated the inter and intra-rater agreements in assessing MIBG H/M ratios. Results: A moderate agreement in the raters’ classification of pathological and non-pathological scores emerged regarding early and late H/M ratio values (κ=.45 and .69 respectively), applying the manual method, while the early and late H/M ratios obtained with the semiautomatic method reached a good agreement among observers (κ=.78). Cohen-Kappa values revealed that the semiautomatic method improved the agreement between expert and inexpert raters: the agreement improved from a minimum of 0.29 (fair, for early H/M) and 0.69 (substantial, in late H/M) with the manual method, to 0.90 (perfect, in early H/M) and 0.87 (perfect, in late H/M) with the semiautomatic method. Conclusion: The use of the semiautomatic method improves the agreement among raters in classifying’ H/M ratios as pathological or non-pathological, namely for inexpert readers. These results have important implications for semi-quantitative assessment of MIBG images in clinical routine.